[English original] Influence of Physical Complaints on Workload and Readiness-to-Train in U23 Footballers: A Preparatory Period for The Olympic Games - Vasquez Bonilla, Aldo A. (2025)
This study examined the relationship between physical complaints on training load and readiness-to-train in footballers during shock microcycles and tapering periods leading up to the Olympic Games. Twenty-six under-23 footballers from the Honduras National Team participated (age: 22.5 ± 1.8 years). The external load was evaluated using global positioning system, and maximal speed (km/h), sprinting distance (>24.1 km/h), very high-intensity running distance (18.1-24 km/h), high-intensity running distance HID (15.1-18 km/h), player load, number of accelerations (+2.5 m/s²) and decelerations (-2.5 m/s²) were obtained. In addition, subjective measures such as the perceived rating exertion and the total quality of recovery scale were performed. A readiness-to-train questionnaire, encompassing mood, sleep quality, energy levels, muscle pain, nutrition, stress, and health was administered. Physical complaints were identified using the Oslo Sports Trauma Research Center questionnaire. The findings show the presence of physical complaints in both the load accumulation and the tapering periods. Footballers who experienced physical complaints showed lower perceived exertion, higher muscle soreness and poorer sleep quality, health, and motivation. Also, lower performance was demonstrated in maximal speed, sprinting, accelerations, and decelerations. Sports scientists should closely monitor physical complaints in national football teams and prevent injuries before long-duration events such as the Olympic Games.